VALIDITY AND PRACTICALITY OF A COGNITIVE CONFLICT-BASED ELECTRONIC ASSESSMENT ON WORK AND ENERGY TO EVALUATE HIGH SCHOOL STUDENTS’ CRITICAL THINKING SKILLS - Amalia Salsabila; Fatni Mufit; Yenni Darvina; Emiliannur Emiliannur (Physics Learning and Education, 2026)
The integration of information and communication technology (ICT) in education has encouraged the use of electronic assessments to support the evaluation of higher-order thinking skills, particularly critical thinking in physics learning. However, existing assessments are still limited in effectively measuring these skills. This study aims to develop a cognitive conflict-based electronic assessment on work and energy and to determine its content validity and practicality in evaluating high school students’ critical thinking skills. This study employed a Research and Development (R&D) method using Plomp’s model, which consists of preliminary research, development or prototyping, and assessment stages. The subjects were physics teachers and students of State Senior High School 10 Padang with varying levels of critical thinking skills. The instruments included a validation sheet and a practicality questionnaire. Content validity was analyzed using Aiken’s V index, while practicality was analyzed using percentage techniques. The results showed that the developed assessment has a high level of content validity, with an average Aiken’s V value of 0.85, categorized as “highly valid,” and is highly practical, with scores above 96% across all evaluation stages. Therefore, the assessment is suitable for evaluating students’ critical thinking skills in physics learning and can be used as an effective tool to support the improvement of learning evaluation quality.